2019
DOI: 10.3390/su11184929
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Leading Factors in Energy-Related CO2 Emissions Change among Subregions of the Beijing–Tianjin–Hebei Area from 2006 to 2016: An Extended LMDI Analysis

Abstract: In recent decades, the Beijing–Tianjin–Hebei (BTH) region has experienced rapid economic growth accompanied by increasing energy demands and CO2 emissions. Understanding the driving forces of CO2 emissions is necessary to develop effective policies for low-carbon economic development. However, because of differences in the socioeconomic systems within the BTH region, it is important to investigate the differences in the driving factors of CO2 emissions between Beijing, Tianjin, and Hebei. In this paper, we cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Cities are the key areas in which to implement carbon emission popular alternative method. Index decomposition analysis (IDA) [30][31][32][33][34][35] and structural decomposition analysis (SDA) [36][37][38][39][40][41] are mainly employed. IDA can only measure the direct production effect, while SDA can capture the direct and indirect production effects by taking inter-industrial interactions into consideration [6].…”
Section: Introductionmentioning
confidence: 99%
“…Cities are the key areas in which to implement carbon emission popular alternative method. Index decomposition analysis (IDA) [30][31][32][33][34][35] and structural decomposition analysis (SDA) [36][37][38][39][40][41] are mainly employed. IDA can only measure the direct production effect, while SDA can capture the direct and indirect production effects by taking inter-industrial interactions into consideration [6].…”
Section: Introductionmentioning
confidence: 99%
“…In more than half of these provinces, the effect changed from promotion to inhibition from 2008–2012 to 2012–2016. It was reported that R&D intensity presented an obvious mitigating effect in SH [ 14 ], HB [ 19 ] and on the national level [ 15 ]. Taken together, the effect of R&D intensity varied considerably, which may be associated with changes in the performers of R&D activities [ 17 ] and technical barriers.…”
Section: Resultsmentioning
confidence: 99%
“…An extended LMDI model [ 19 ] was used to break down the IECE changes into the following nine factors: …”
Section: Methodology and Data Sourcementioning
confidence: 99%
See 1 more Smart Citation